2017
DOI: 10.1021/acs.joc.7b01947
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Organophosphorus Compounds through Copper-Catalyzed Annulation Involving C–O and C–P Bond Formations

Abstract: A novel copper(II) trifluoromethanesulfonate-catalyzed, high-efficiency, and atom-economical synthesis of valuable organophosphorus compounds via cascade annulation of propargylic alcohols with diphenylphosphine oxide is described. This protocol, which has a good functional-group compatibility and insensitivity to an ambient atmosphere, provides a simple and direct pathway to the products, organophosphorus compounds, in good yields under mild conditions. The method could be efficiently scaled up to gram scale,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…As for the synthesis of phosphorylated heterocycles, there are only three reports concerning the dehydrative cyclization of propargylic alcohols with P(O)−H species. In 2017, the Liang group established a novel Cu(OTf) 2 ‐catalyzed cascade annulation of 3‐(2‐hydroxyphenyl)‐1,1‐diarylprop‐2‐yn‐1‐ols 574 with diarylphosphine oxides, furnishing the benzofuran‐3‐yldiarylphosphine oxides 575 that act as important skeletons in a number of natural products and bioactive molecules (Scheme ) . Mechanistic studies suggested that the reaction proceeded with an initial coordination of Cu(OTf) 2 to propargylic alcohol 574a leading to intermediate 576 , which underwent a subsequent intermolecular attack by Ph 2 P(O)H to produce the stabilized allenic intermediate 577 .…”
Section: Reactions Involving Heterocyclic Ring Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the synthesis of phosphorylated heterocycles, there are only three reports concerning the dehydrative cyclization of propargylic alcohols with P(O)−H species. In 2017, the Liang group established a novel Cu(OTf) 2 ‐catalyzed cascade annulation of 3‐(2‐hydroxyphenyl)‐1,1‐diarylprop‐2‐yn‐1‐ols 574 with diarylphosphine oxides, furnishing the benzofuran‐3‐yldiarylphosphine oxides 575 that act as important skeletons in a number of natural products and bioactive molecules (Scheme ) . Mechanistic studies suggested that the reaction proceeded with an initial coordination of Cu(OTf) 2 to propargylic alcohol 574a leading to intermediate 576 , which underwent a subsequent intermolecular attack by Ph 2 P(O)H to produce the stabilized allenic intermediate 577 .…”
Section: Reactions Involving Heterocyclic Ring Formationmentioning
confidence: 99%
“…Compared to the previous case, the differences in the reaction mechanisms lie in the intramolecular attack of the OH group to the terminal carbon of allenic intermediate 582 to afford 6‐ endo ‐ trig cyclization intermediate 583 , which is further transformed to product 581a via a protonation process (Scheme ).…”
Section: Reactions Involving Heterocyclic Ring Formationmentioning
confidence: 99%
“…Previous methods for the preparation of such compounds often suffered from some limitations such as poor substrate scope, complex or well‐defined ligands and the need for prefunctionalized starting materials. Recently, the groups of Gao, Yang, Liang, and Shen have independently reported the metal‐catalyzed direct dehydrative cross‐coupling reaction of unprotected propargylic alcohols and P(O)−H compounds, which provided a general, convenient, step‐ and atom‐economic procedure for accessing allenylphosphoryl compounds. In Gao's work, it was found that the use of 30 mol% of Cu(OTf) 2 as Lewis acid catalyst allowed the reaction to proceed smoothly at 100 °C with both unprotected terminal or internal secondary propargylic alcohols and disubstituted phosphine oxides, phosphinates or phosphonates (Scheme ).…”
Section: C(alkenyl)−p Bond Formationmentioning
confidence: 99%
“…Later the Liang group performed the reaction of substituted 3‐(2‐aminophenyl)‐1,1‐diphenylprop‐2‐yn‐1‐ols ( 74 ) with diphenylphosphine oxide ( 2a ) by using a catalyst consisting of 15 mol% of Cu(OTf) 2 and 50 mol% of Ag 2 CO 3 in ClCH 2 CH 2 Cl at 90 °C, furnishing diphenyl(propa‐1,2‐dien‐1‐yl)phosphine oxides 75 in moderate to good yields (Scheme ) …”
Section: C(alkenyl)−p Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation